2018
DOI: 10.1111/jam.13907
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study on the occurrence in pigs of colistin‐resistant Escherichia coli carrying mcr‐1 following the cessation of use of colistin

Abstract: The results suggest that cessation of colistin use may help over time to reduce or possibly eliminate mcr-1 E. coli on pig farms where it occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Thus, ciprofloxacin plates enabled detection not only of ciprofloxacin resistant E. coli, most often with QRDR mutations, but additional AMR genes. Furthermore, these MDR E. coli were less likely to be detected on other plates because they probably represented a small percentage of the total E. coli, as previously shown for mcr-harboring E. coli isolated from pig farms (Randall et al, 2018). QRDR mutations in Salmonella can confer protection against other antimicrobials (Webber et al, 2013) and the presence of double-serine QRDR mutations (GyrA83Ser and ParC80Ser) confers a selective advantage in lineages of several bacterial pathogens (Fuzi et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, ciprofloxacin plates enabled detection not only of ciprofloxacin resistant E. coli, most often with QRDR mutations, but additional AMR genes. Furthermore, these MDR E. coli were less likely to be detected on other plates because they probably represented a small percentage of the total E. coli, as previously shown for mcr-harboring E. coli isolated from pig farms (Randall et al, 2018). QRDR mutations in Salmonella can confer protection against other antimicrobials (Webber et al, 2013) and the presence of double-serine QRDR mutations (GyrA83Ser and ParC80Ser) confers a selective advantage in lineages of several bacterial pathogens (Fuzi et al, 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Some studies have proved that stopping using colistin in positive mcr-1 carriers porcine farms has resulted in the disappearance of the resistance (Randall et al, 2018). However, because of the MDR profile of our ST131 isolates, this might not be that easy, due to coselection by other antimicrobials and host fitness adaptation.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, in vitro studies on Pseudomonas aeruginosa have shown that colistin-resistant phenotypes may become susceptible to colistin after a series of passages in colistin-free medium (Lee et al, 2016), which may also occur for E. coli and Salmonella. In addition, some field epidemiological studies also suggest that cessation of colistin use may help over time to reduce the frequency of detectable colistin resistance, and of mcr-1 gene, carried by Enterobacteriaceae in pigs (Randall et al, 2018;Wang et al, 2020), likely because its presence would be associated with a significant biological fitness cost (Nang et al, 2018). However, considering that the mcr-1 gene has been also detected in colistin-susceptible Enterobacteriaceae (Ovejero et al, 2017;Pham Thanh et al, 2016), and that we only tested the presence of mcr genes on those isolates with MIC >1 mg/L, it is possible that we may have somewhat overlooked the presence of dormant mcr-1 genes in some of the susceptible isolates.…”
Section: Discussionmentioning
confidence: 99%